Meningkatkan Pengetahuan Remaja tentang Kenakalan dan Perilaku Berisiko melalui Pendidikan Pencegahan: Studi Berbasis Komunitas di Sekolah Asrama Muhammadiyah Selong - Ulyani, Maya; Khotmi, Nurmaulia; Fitri, Elisa Sulistia; Mardani, Riasari; Hartiani, Hartiani; Mandala, Yenny (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Adolescence is a crucial transitional phase in the human life cycle, characterized by rapid biological, cognitive, and emotional changes. Psychologically, this stage is often associated with a period of storm and stress, during which individuals experience emotional instability due to simultaneous physical, social, and psychological transformations. Such conditions make adolescents particularly vulnerable to negative environmental influences that may lead to delinquency and risky behaviors if not properly addressed. This community service activity introduces an integrative approach that combines preventive education with psychoeducation to support adolescents in understanding and preventing such behaviors. The objective of this activity is to describe the implementation of preventive education and to explore participants’ responses and engagement during the program. The activity employed a preventive health education approach delivered through direct face-to-face interaction at Muhammadiyah Boarding School (MBS), East Lombok. Participants consisted of 35 students, both male and female, accompanied by two teachers. Observational findings indicated a high level of enthusiasm and engagement throughout the activity. This was reflected in students’ active participation during ice-breaking sessions, discussions, and question-and-answer interactions, which contributed to an interactive and supportive learning environment. Students demonstrated responsiveness to the material presented, indicating an increased awareness and understanding of delinquency and risky behaviors. These findings suggest that interactive and participatory educational methods are well-received and can support adolescents’ awareness. However, further evaluation using structured measurement tools is recommended to assess outcomes more comprehensively.